2015
DOI: 10.1242/jeb.118414
|View full text |Cite
|
Sign up to set email alerts
|

Social dominance and reproductive differentiation mediated by dopaminergic signaling in a queenless ant

Abstract: In social Hymenoptera with no morphological caste, a dominant female becomes an egg layer, whereas subordinates become sterile helpers. The physiological mechanism that links dominance rank and fecundity is an essential part of the emergence of sterile females, which reflects the primitive phase of eusociality. Recent studies suggest that brain biogenic amines are correlated with the ranks in dominance hierarchy. However, the actual causality between aminergic systems and phenotype (i.e. fecundity and aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 80 publications
1
50
0
Order By: Relevance
“…Each colony was reared in plastic artificial nests filled with moistened plaster. This rearing method and the general biology of this species are available in [20,22]. The nests were maintained at 258C under 16 L : 8 D (light phase, 0700 -2300).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each colony was reared in plastic artificial nests filled with moistened plaster. This rearing method and the general biology of this species are available in [20,22]. The nests were maintained at 258C under 16 L : 8 D (light phase, 0700 -2300).…”
Section: Methodsmentioning
confidence: 99%
“…Diacamma colonies consist of one mated egg-layer (i.e. gamergate) and 30 -200 workers which perform agedependent division of labour [19,20]. Their nurses exhibit clear circadian activity rhythms when individually isolated from a colony (active in daytime) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Five orphan colonies (lacking gamergates), each containing 15 workers, were made from three original colonies, as described previously (Okada et al . , ). Under natural conditions, such small colonies are often observed, and they are probably excavated soon after fission (Y. Okada, personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…(a) If a callow female retains the wing‐like appendages called ‘gemmae’, she becomes a future reproductive so that her aggressive dominance behaviour remains at a high level [red dashed line (Okada et al . ), and her ovaries rapidly develop (red solid line and illustration (Okada et al . )].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that DA plays an important role in social hierarchy of ants, with DA concentration significantly higher in socially dominants than subordinates (Penick et al, 2014; Okada et al, 2015). A similar observation has also been reported in a bird such as ring-necked phesants, with higher social rank males exhibiting higher striatal DA concentration (Mcintyre and Chew, 1983).…”
Section: Roles Of Da In Social Functionmentioning
confidence: 99%